2014
DOI: 10.1039/c4ob00474d
|View full text |Cite
|
Sign up to set email alerts
|

Bis-chlorination of a hexapeptide–PCP conjugate by the halogenase involved in vancomycin biosynthesis

Abstract: Vancomycin is an important nosocomial antibiotic containing a glycosylated, cross-linked and doubly chlorinated heptapeptide backbone. During the biosynthesis of the vancomycin aglycone, two β-hydroxytyrosine (Bht) residues are inserted at positions-2 and -6 into the heptapeptide backbone by a non-ribosomal peptide synthetase. A single flavin-dependent chlorinase (VhaA) is responsible for chlorinating both Bht residues at some ill-defined point in the assembly process. We show here using in vitro assays that V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 30 publications
1
40
1
6
Order By: Relevance
“…151 This study demonstrated, for the first time, that halogenation in biosynthesis of 3 occurs en route the NRPS assembly of the linear heptapeptide. A biomimetic CP-loaded hexapeptide substrate was dichlorinated by VhaA.…”
Section: Flavin-dependent Halogenasesmentioning
confidence: 69%
“…151 This study demonstrated, for the first time, that halogenation in biosynthesis of 3 occurs en route the NRPS assembly of the linear heptapeptide. A biomimetic CP-loaded hexapeptide substrate was dichlorinated by VhaA.…”
Section: Flavin-dependent Halogenasesmentioning
confidence: 69%
“…1b). 18 Late-stage halogenation of complex molecules is particularly challenging, but tethering a substrate to a carrier protein presents its own biosynthetic demands. Numerous fungal FDHs that react with freestanding complex molecules have been identified, 1924 including MalA which is a late-stage halogenase involved in malbrancheamide biosynthesis (Fig.…”
Section: Bioactive Halogenated Natural Products and Halogenating Enzymesmentioning
confidence: 99%
“…A number of putative phenolic halogenases such as Clo-Hal (involved in the biosynthesis of chlorobiocin (46) in Streptomyces roseochromogenes), 197,198 BhaA (from the balhimycin (47) biosynthetic pathway in Amycolatopsis mediterranei), [199][200][201] and ComH (responsible for chlorination en route to complestatin (46) in Streptomyces lavendulae) [202][203][204] have been identified (Figure 17). Whilst further in vitro studies are required to elucidate the true substrates of these enzymes, it is likely that Clo-Hal, BhaA and ComH are all Class B, carrier protein-dependent, phenolic halogenases.…”
Section: Predicted Class B Phenolic Halogenasesmentioning
confidence: 99%
“…197 The location of the BhaA encoding gene in the balhimycin gene cluster, alongside NRPS encoding genes, and in vitro experiments also suggest that BhaA halogenates a PCP tethered tyrosine or β-HT intermediate. [199][200][201][202][203][204][205] The halogenase (Tcp21) in the teicoplanin gene cluster of Actinoplanes teichomyceticus is similarly predicted to process a Tyr-or β-HT-S-PCP substrate. [205][206][207] Crystallography of the related chondrochloren halogenase CndH, revealed that the substrate for CndH may also be a tyrosine-related intermediate that is most likely PCP tethered.…”
Section: Predicted Class B Phenolic Halogenasesmentioning
confidence: 99%